Design and construction of a portable apparatus to measure thermal conductivity - Cuenca M.H. (2021)
The characterization of the thermal insulation properties of construction materials represents a fundamental step on building insulation assessment. The present work aims to design and build a portable apparatus, namely, Portable LAMBDA UNI, capable of measuring the thermal conductivity of insulation materials. This portable apparatus is based on the standard ASTM C 518, which is a secondary method for measuring thermal conductivity. The apparatus also measures the effective thermal conductivity of square prism thermal insulation materials of 60 mm per side and a maximum thickness of 14 mm. The thermal conductivity of the drywall and adobe with Stipa ichu was measured with the Portable LAMBDA UNI, with the values being 0.265 W m-1 K-1and 0.357 W m-1 K-1, respectively. © 2021 Published under licence by IOP Publishing Ltd.